2013
DOI: 10.2341/12-335-c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Activation, Agent Concentration, and Tooth Thickness on Dental Sensitivity After Bleaching

Abstract: Increases in the concentration of bleaching agents directly affect tooth sensitivity, and LED/laser activation and tooth thickness are not correlated with tooth sensitivity after dental bleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 44 publications
4
56
1
5
Order By: Relevance
“…30 Similarly, a clinical study 31 that evaluated TS in patients treated with different bleaching techniques found that the highest TS values occurred with in-office bleaching using 35% HP (two sessions, 45 minutes each) compared with at-home bleaching with 10% CP (8 hours daily for two weeks). In contrast, Reis; Kossatz and Martins 28 showed that TS after two in-office bleaching sessions with two concentrations of HP was relatively low; however, this result can be because the tested products contained 2% calcium gluconate as a desensitizing agent.…”
Section: Discussionmentioning
confidence: 96%
“…30 Similarly, a clinical study 31 that evaluated TS in patients treated with different bleaching techniques found that the highest TS values occurred with in-office bleaching using 35% HP (two sessions, 45 minutes each) compared with at-home bleaching with 10% CP (8 hours daily for two weeks). In contrast, Reis; Kossatz and Martins 28 showed that TS after two in-office bleaching sessions with two concentrations of HP was relatively low; however, this result can be because the tested products contained 2% calcium gluconate as a desensitizing agent.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9] These concentrations show similar effectiveness, and in some cases, much lower adverse post-procedure effects. However, only one report 10 have used a concentration permitted by the European Community.…”
Section: Introductionmentioning
confidence: 89%
“…3,4,5,6 Researchers have used clinical or in vitro studies to obtain data that can Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%